Mengukur Manfaat Ekonomis Sistem Aplikasi Monitoring ATM dengan Metode Information Economics: Studi Kasus PT Bank XYZ Tbk - Viany Utamy Thjin; Hudiarto Hudiarto; Intan Puspita (Bina Nusantara University, 2005)
Research discusses information economics method to measure the economic benefit from information technology application. Research with information economics method is applied on Gasper Vantage, ATM monitoring application system that is used by XYZ Bank Company. The Gasper Vantage is applied to increase the ATM availability and to give a better service to customer. From the research, the Gasper Vantage can be useby XYZ Bank Company and also increasing the company competitive advantage.